Detection of nontuberculous mycobacteria from water buffalo raw milk in Brazil - Jordao, C. M. [UNESP]; Lopes, F. C. M. [UNESP]; David, S.; Farache Filho, Adalberto [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2009)
Milk is an important nutritional source to man and water buffalo raw milk is used to produce mozzarella cheese. Products from unpasteurized milk have been associated with certain infectious diseases and can carry pathogenic mycobacteria. Nontuberculous mycobacteria (NTM) are emerging pathogens causing opportunistic infections in humans and animals. The objectives of this study were to demonstrate the presence of mycobacteria in water buffaloes' milk and to determine their role as possible sources of NTM infections. In this study, raw milk samples from dairy water buffaloes (Bubalus bubalis) (N = 23) were decontaminated by Petroff method and inoculated on to Lowenstein-Jensen and Stonebrink medium. After confirming positive colonies for acid fast bacilli (AFB) by Ziehl-Neelsen technique, the isolated mycobacteria were identified by PCR-Restriction Enzyme Analysis (PRA) and mycolic acids analysis by thin-layer chromatography (TLC). Mycobacterium simiae (2 isolates), Mycobacterium kansasii (2 isolates), Mycobacterium flavescens (2 isolates), Mycobacterium gordonae (3 isolates) and Mycobacterium lentiflavum (I isolate) were identified by these techniques. The isolation of opportunistic pathogens such as M. kansasii, M. simiae and M. lentiflavum from raw milk represent a risk for the consumers of mozzarella cheese made by this milk. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Milk; Mycobacteria; Water buffalo; PRA; NTM; Mycolic acids